Under the volcano - Lowry, Malcolm, 1909-1957. (New York : Perennial Classics, 2000)
On a single, fateful day in Quauhnahuac, Mexico, 1938, a former British consul wrestles with his demons as his wife tries to rescue their marriage from his drinking problem -- On the Day of the Dead, in 1938, Geoffrey Firmin, an alcoholic and ruined man, is fatefully living out his last day, drowning himself in mescal while his former wife and half-brother look on, powerless to help him. The events of this one day unfold against a backdrop unforgettable for its evocation of a Mexico at once magical and diabolical.
Originally published: J.B. Lippincott, 1947.
1
Keywords: Alcoholics -- Fiction; Consuls -- Fiction; British -- Mexico -- Fiction; Cuernavaca (Mexico) -- Fiction; All Souls$1 (BDay s -- Fiction; Psychological fiction